The effect of temporal leadership on quiet quitting among primary healthcare workers: the chain-mediating role of time management competency and work-family enrichment and moderating role of organizational communication - Xu, Qianqian; Yu, Zhikai; Fan, Si; Wu, Yuanyang; Wang, Yanting; Zou, Dongdong; Hu, Jinwen; Zhang, Xinping (Frontiers in psychology, 2025)
Quiet quitting among primary healthcare (PHC) workers is prevalent and seriously reducing healthcare productivity and quality. Temporal leadership takes advantage of effective time scheduling, which can avoid unreasonable working arrangements and then mitigate quiet quitting. However, there is little known about the influence and mechanism of temporal leadership on quiet quitting. This study aims to explore the influencing mechanism of temporal leadership on quiet quitting among PHC workers, in addition to test the chain-mediating roles of time management competency and work-family enrichment of PHC workers, as well as the moderating roles of organizational communication. An on-site survey of 520 PHC workers was conducted in a health reform area. The participants were asked to complete five self-report questionnaires, including Temporal Leadership Scale (TLS), Time Management Scale (TMS), Work-Family Enrichment Scale (WFES), Quiet Quitting Scale (QQS), and organizational Culture Scale (OCS). Temporal leadership, time management, and work-family enrichment all significantly and negatively predict quiet quitting among PHC workers. Time management and work-family enrichment played the chain-mediating roles between temporal leadership and quiet quitting. The relationship between temporal leadership and time management was moderated by organizational communication. Temporal leadership can mitigate quiet quitting among PHC workers by enhancing their time management competencies and work-family enrichment, and high levels of organizational communication can strengthen the effect of temporal leadership on time management competency. These findings highlight the importance of temporal leadership in health systems and provide an evidence-based strategy for leaders to effectively address quiet quitting.